Magnetization reversal dependence on effective magnetic anisotropy in electroplated Co–Cu nanowire arrays. Issue 18 (14th May 2015) - García, J.; Prida, V. M.; Vivas, L. G.; Hernando, B.; Barriga-Castro, E. D.; Mendoza-Reséndez, R.; Luna, C.; Escrig, J.; Vázquez, M.
<x xml:space="preserve">Abstract</x> Arrays of Co(100−x)Cu(x) (0 ≤ x ≤ 27) nanowires with 45 nm of diameter and 18 μm in length, have been potentiostatically electrodeposited into the hexagonally self-assembled nanopores of anodic alumina membranes.